2009
DOI: 10.1016/j.juro.2009.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Nonmuscle Invasive Bladder Cancer Recurrence and Progression in Patients Treated With Bacillus Calmette-Guerin: The CUETO Scoring Model

Abstract: We propose a scoring model to stratify the risk of recurrence and progression in patients treated with bacillus Calmette-Guerin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
336
3
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(390 citation statements)
references
References 19 publications
9
336
3
19
Order By: Relevance
“…3 In 2011, Rosevear et al validated the CUETO tables for recurrence in their series of 718 patients treated with BCG plus interferon α-2B. 4 In the present study, the CUETO system has been shown to be appropriate for predicting tumor recurrence and progression for patients with BCG instillation therapy in a Japanese cohort.…”
Section: Conflict Of Interestmentioning
confidence: 54%
“…3 In 2011, Rosevear et al validated the CUETO tables for recurrence in their series of 718 patients treated with BCG plus interferon α-2B. 4 In the present study, the CUETO system has been shown to be appropriate for predicting tumor recurrence and progression for patients with BCG instillation therapy in a Japanese cohort.…”
Section: Conflict Of Interestmentioning
confidence: 54%
“…9 The sources of recurrence are implantation during TUR, persisting CIS, and preclinical lesions. 3,10,11 In high-risk NMIBC, intravesical BCG is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Progression was defined as muscular invasion or metastatic disease. The clinical and pathological progression risk was calculated using two multivariate risk assessment tools, the European Organization for Research and Treatment of Cancer (EORTC) risk tables and the Spanish Urological Club for Oncological Treatment (CUETO) prognostic scoring model (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a significant concordance between pathological aggressive phenotype and molecular progression risk score was observed, and patients with aggressive bladder tumors exhibited increased molecular progression risk scores. Notably, the molecular progression risk score was significantly associated with clinicopathological multivariate progression models, including the EORTC and CUETO risk tables (13,14). Thus, a molecular progression risk score based on gene expression may represent biological aggressiveness, even in the absence of clinical information.…”
Section: Multivariate Analysis As Amentioning
confidence: 99%
See 1 more Smart Citation